L-asparaginase Conjugates of Rhodospirillum Rubrum with Polymers of Different Structures with Improved Biocatalytic Properties - Dobryakova, N.V.; Zhdanov, D.D.; Kudryashova, E.V. (Biomedical Chemistry: Research and Methods, 2024)
L-asparaginase from the mesophyllic bacterium Rhodospirillum rubrum shows promise as a potential biomedicine treatment for tumor diseases. To enhance the enzyme’s catalytic parameters, we have synthesized covalent conjugates with chitosan-PEG, chitosan-glycol and polyethylenimine. Interestingly, binding to these polymers had minimal impact on the enzyme's substrate binding constant. The RrA-PEI conjugate showed the most significant changes in secondary structure content. The success of the previous modification was evaluated by IR spectroscopy, which indicated that the polycations used in the work have a positive effect on the catalytic activity of the enzyme. The RrA-chitosan-PEG conjugate demonstrated the highest enzymatic activity.